Investigating the Effect of Internet Assisted Sight Translation on the Students’ Speaking Fluency at University of Muhammadiyah Sumatera Utara - Nasution, Dewi Kesuma (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
This paper seeks to investigate the effect of internet assisted sight translation on the students’ speaking fluency. Students at the third year of English Education Department were involved in this study. The data were collected using audio-recording and questionnaires. As a form of tasks, students were asked to translate orally Indonesia’s tourism destinations texts which are derived from the internet for the course of eight meetings. Students’ speaking fluency was assessed through the criteria of excellent, good, average and poor are used. The findings revealed that students at the experimental class gained a significant effect in terms of their speaking fluency. Upon the treatment, students at the experimental class showed an effect in terms of their speaking fluency. Approximately 90% of students are rated good, and the remaining 10% is rated average. Hence, it can be concluded that internet assisted sight translation gives effect the students’ speaking fluency.